Insights into uveitis from Brentuximab vedotin in refractory Hodgkin’s lymphoma: a case report and brief review - Liu, Mengyuan; Ren, Kexing; Ai, Ping; Zou, Liqun (Frontiers in Oncology, 2024)
This case report describes a 16-year-old patient with refractory Hodgkin’s lymphoma who developed bilateral anterior and intermediate uveitis as an adverse reaction to Brentuximab vedotin (BV). This is a rare case of an ocular adverse reaction potentially related to BV, with symptoms like blurred vision, decreased visual acuity, photophobia, and redness. Potential mechanisms include BV targeting CD30+ T cells in the uveal tissue or an immune response triggered by the microtubule-disrupting agent MMAE within BV. This highlights the need for vigilant monitoring of ocular adverse events in BV-treated patients and further research into their mechanisms and management.